DOWNSCOPING: How to Tame the Diversified FirmDOWNSCOPING: How to Tame the Diversified Firm, by HoskissonRobert E. and HittMichael A., New York: Oxford University Press, 1994. - Grant, John H. (Academy of Management Review, 1996)
The article reviews book ?Downscoping: How to Tame the Diversified Firm,? by Robert E. Hoskisson and Michael A. Hitt.